The treatment of hypertension in people with dementia: a systematic review of observational studies - Welsh, Tomas; Gladman, John R.F.; Gordon, Adam L. (Biomed Central, 2014)
Background Hypertension is very common in older people and a number of trials of antihypertensives have demonstrated benefit from treatment in even the oldest old. However, people with dementia were significantly under-represented in these studies and as a population are more likely to be physically frail, to suffer orthostatic hypotension and to experience adverse effects from polypharmacy at a lower drug count. It may be that different thresholds for commencement and cessation of treatment should be considered and may already be used for this group. Against this background this review sets out to describe the prevalence of hypertension in people with dementia, its treatment, change in treatment over time and the achievement of blood pressure (BP) control.